Factors influencing how senior nurses and midwives acquire and integrate coaching skills into routine practice: a grounded theory study. (6th January 2015) - Rafferty, Rae; Fairbrother, Greg
Abstract Aim To introduce a theory which describes the process of and explicates the factors moderating, the acquisition and integration of leadership coaching skills into the routine practice of senior nurses and midwives. Background Organizations invest significant resources in leadership coaching programs to ensure that coaching is embedded as a core function of the manager's role. However, even after training, many managers remain unable to undertake this role successfully. The process by which health professionals translate 'manager as coach' training into successful practice outcomes, has remained largely unexplored. Design A grounded theory study design. Methods Data, collected between February 2012–May 2013, included in‐depth interviews with 20 senior nurses and midwives who had attended a leadership coaching program and analysis of nine reflective practice journals. Multiple researchers coded and analysed the data using constant comparative techniques. Results The outcomes of coaching training ranged from inappropriate use of the coaching skills through to transformed managerial practice. These outcomes were influenced by the dynamic interaction of three central domains of the emergent theoretical model: pre‐existing individual perceptions, program elements and contemporaneous experiences. Interactions occurred within the domains and between them, impacting on activators such as courage, motivation, commitment and confidence. Conclusion The study offers new insights into how senior nurses and midwives acquire and integrate coaching skills into their routine practice. The process is described as multifactorial and dynamic and has implications for the training design, delivery and organizational support of future leadership coaching programs.